Construction and application of bionic antifouling coatings inspired by soft coral. Issue 3 (19th August 2022) - Bing, Wei; Jin, E.; Tian, Limei; Jin, Huichao; Liu, Zhuo
Abstract: Marine biofouling will bring a series of environmental and social problems, which restrict the development and utilisation of marine resources. Therefore, how to prevent biofouling has become a global issue. With the exploration of antifouling methods, bionic antifouling technology with environmentally friendly, broad‐spectrum, and long‐term advantages has gradually attracted people's attention. Inspired by the antifouling strategy of soft coral ( Sarcophyton trocheliophorum ), the silicone rubber (RTV‐2) with similar elasticity to coral skin was selected as the substrate. The composite structure of the upper transparent layer and the lower porous layer was prepared by simulating the structure of soft coral as the structural factors of the bionic antifouling coatings. Meanwhile, several organic antifouling components with high content contained in soft coral were added to the transparent layer and porous layer, respectively, as the component factors of biomimetic coatings. The bionic antifouling coatings, which are highly consistent with the coral structure, obtained the best antifouling performance under static and dynamic conditions. The above results provide new ideas for the synthesis of environmentally friendly bionic antifouling coatings.